Evaluation of flocs resistance and reflocculation capacity using the LDS technique - Rasteiro, M. G. (2008)
In a previous paper we have shown the added value of using LDS to monitor flocculation. It can supply, simultaneously, information on flocs size and structure and enlighten flocculation kinetics and mechanisms. In this paper, LDS is applied to study deflocculation and reflocculation processes of precipitated calcium carbonate (PCC) induced by cationic polyacrylamides, when different types of shear forces are applied. LDS can detect the influence of polymer characteristics and concentration as well as of the type of shearing, on flocs resistance and reflocculation degree, which depend on flocs structure and on the type of bonds between particles. As expected, flocs formed by bridging mechanism reflocculate with difficulty while flocs formed by patching reflocculate to a higher degree. Flocs resulting from reflocculation are more compact than the original ones, as assessed by the mass fractal dimension. Reflocculation is also lower when the flocs are submitted to superficial shearing than when they are submitted to sonication. Shearing induced by sonication is sufficient to break down the flocs in many fragments while the increase of pump speed only detaches particles by erosion, at the flocs surface, where bonds are weaker. Results prove that LDS is useful to monitor deflocculation and reflocculation processes and to predict floc resistance under different conditions. Moreover, the whole study demonstrates the benefit of using LDS for a complete evaluation of flocculants performance in the different stages of flocculation: aggregation, stabilization, deflocculation and reflocculation.